PENINGKATAN PEMAHAMAN MAKNA SURAH AL-’ALAQ DI SD NEGERI 054876 CINTA DAPAT KELAS 3 BERBASIS PROBLEM BASED LEARNING (PBL) - Arinawiyati (Journal of Community Devation, 2024)
The current problem faced in the education sector is the low understanding of students regarding religious values and ethics. One of the efforts to address this issue is through Islamic Religious Education, which plays a crucial role in shaping students' character and instilling essential spiritual and ethical values for daily life. In the third grade of SD Negeri 054876 Cinta Dapat, students' comprehension of the meaning of Surah Al-‘Alaq has not yet reached the expected level. This Surah contains significant messages about the importance of reading and learning as forms of devotion to God. However, students' understanding of these meanings remains low, necessitating a more effective learning approach. This research aims to enhance students' understanding of Surah Al-‘Alaq through the Problem Based Learning approach. The research method employed is Classroom Action Research, conducted in two cycles involving planning, implementation, observation, and reflection stages. Data collection was carried out through observations, documentation, and written tests to assess students' understanding related to Surah Al-‘Alaq. The results indicate that the implementation of the PBL model can improve students’ comprehension of Surah Al-‘Alaq. This improvement is reflected in the increase of students achieving good and very good comprehension categories from 60% in the first cycle to 80% in the second cycle. It is concluded that PBL is effective in enhancing students' understanding of religious education material while instilling deeper ethical and scientific values. It is recommended that PBL activities be combined with more creative and engaging tasks to motivate students in their learning process